2015
DOI: 10.1071/he15020
|View full text |Cite
|
Sign up to set email alerts
|

Smoking among Aboriginal adults in Sydney, Australia

Abstract: Issue addressed Tobacco consumption contributes to health disparities among Aboriginal Australians who experience a greater burden of smoking‐related death and diseases. This paper reports findings from a baseline survey on factors associated with smoking, cessation behaviours and attitudes towards smoke‐free homes among the Aboriginal population in inner and southwestern Sydney. Methods A baseline survey was conducted in inner and south‐western Sydney from October 2010 to July 2011. The survey applied both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The intention to quit remained high among smokers at follow‐up, in line with previous research including the baseline study . Having found high intention to quit at baseline, the project team decided it was important to focus on quit attempts rather than education of the harms of smoking.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The intention to quit remained high among smokers at follow‐up, in line with previous research including the baseline study . Having found high intention to quit at baseline, the project team decided it was important to focus on quit attempts rather than education of the harms of smoking.…”
Section: Discussionsupporting
confidence: 57%
“…This study applied a before and after mixed methods (qualitative and quantitative) evaluation approach. A brief description of the baseline survey has been reported elsewhere outlining the design and implementation and sourcing of questions and participant eligibility criteria. In brief, quantitative data were collected by trained staff using surveys conducted mainly through face‐to‐face interviews and using convenience sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Despite these limitations, a brief or rapid review involving one relevant database over a recent five year period provides useful information on the quantity of research produced in a given setting which was the aim of the review by Eades et al 4 Moreover, one evaluation of four rapid reviews found that their findings, while not as extensive, did not differ greatly from four completed systematic reviews on the same topics. 101 Cross-sectional design Yes a Gardner et al 2015 102 Cross-sectional design No Lalla et al 2015 103 Cross-sectional design Yes Radford et al 2015 104 Cross-sectional design Yes Hopkins et al 2015 105 Cross-sectional design No Arjunan et al 2015 106 Cross-sectional design No Katzenellenbogen et al 2015 107 Cross-sectional design No Pearce et al 2015 108 Cross-sectional design No Spurling et al 2014 109 Cross-sectional design Yes a Scott et al 2014 110 Cross-sectional design No Timms et al 2014 111 Cross-sectional design No Chung et al 2014 112 Cross-sectional design Yes Askew et al 2013 113 Cross-sectional design Yes a Lopez et al 2014 114 Cross 141 Qualitative Yes 153 Mixed methods Yes Gould et al 2015 154 Mixed methods No Jersky et al 2015 155 Mixed methods No Dennis et al 2015 156 Mixed methods No Govil et al 2014 157 Mixed methods Yes Thomas et al 2013 158 Mixed methods No Canuto et al 2013 159 Mixed methods No Homer et al 2012 160 Mixed methods No Larkins et al 2011 161 Mixed methods No Harris et al 2014 162 Cohort study No McDonald et al 2014 163 Cohort study No Jamieson et al 2013 164 Cohort study No Knight et al 2013 165 Cohort study No Webster et al 2013 166 Cohort study No Davis et al 2012 167 Cohort study No Robinson et al 2012 …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%
“…Biddle recommends taking the most efficient approach possible to data collection and analysis in order to minimise participant burden. 180 In summary, research data published in the last five years and indexed on PubMed, 107 Aboriginal health liaison 8,041 b No O'Connor et al 115 Chlamydia 7,103 b Yes Dutton et al 170 Health 128 Albuminuria 860 No Lopez et al 114 Ischaemic heart disease 833 b Yes Hopkins et al 105 Psychological resilience 677 No Arjunan et al 106 Tobacco use 663 No Jamieson et al 164 Oral 113 Stressful events in children 344 b No Lalla et al 103 Oral mucosal disease 342 No Radford et al 104 Dementia 336 No Whish-Wilson et al 99 Birth outcomes 301 Yes Roberts-Thomson et al 117 Oral health 251 No Dorrington et al 174 Pap smears 213 No Gardener et al 102 Children 205 No Wong et al 126 Midwifery 177 Infant health 175 Yes Luke et al 181 Suicidal 169 Breast feeding 159 Yes Webster et al (Gudaga study) 166 Child growth 157 No Scott et al 110 Sexual health 155 No Miller et al (Gudaga study) 118 Child language assessment 150 No Arrow 100 Oral …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%